The understanding of Bioethics: truth-telling to patients of cancer in Pakistani perspective - Abdullah, Amir (International Journal of Endorsing Health Science Research, 2015)
Regardless of advancement in the health care profession, cancer is the leading cause of death. After diagnosing the cancer patient, it is difficult for health care professionals to tell the truth or not. A successful relationship between patients and health care providers depends on the establishment of trust, which is strongly connected with communication based on truth. According to utilitarian argument, it is claimed that health professionals must do something which will produce more relief than anything else that it would render. In utilitarianism moral theory, health professionals will hold morally some right actions which will maximize utility, happiness, welfare and well-being. According to Kant, the consequences are not sufficient for making judgment, and informed consent of disease and treatment must be shared with the patient or family members to maintain the dignity. The doctor needs to minimize his/her personal assumptions in treatment and prognosis.